pola makan makanan cepat saji/instant pada remaja - mahatir muhammad (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
The nutritional needs of adolescents need to be considered because during adolescence there is rapid growth and development. Unhealthy eating habits will affect the nutritional intake of adolescents. Fast food comes from western countries which generally have a high fat and calorie content. Fast food can increase the risk of several diseases, both generative and degenerative diseases such as obesity, diabetes, hypertension, blood lipid disorders or dyslipidemia, cancer, heart disease, and stroke. From the percentage of data acquisition with the level of fast food consumption habits of 67.6%, while the percentage of respondents who have reasons for choosing fast food is more practical by 73% and for good reasons by 27%. This research is a literature review that is reviewed from previously researched journals/articles, journals collected and obtained using several databases including google scholar, and the latest science direct issue from 2014 - 2020 and obtained 15 journals. Which is in accordance with the research topic fast food / instant food patterns in adolescents. Based on the reviewed journals/articles, almost all or most of the results in the literature study were obtained, that most teenagers have a very high frequency of consuming fast food/instant. Adolescence is a period of growth and development. Unhealthy eating habits will affect nutritional intake in adolescents. The wrong diet will have a bad impact and can cause various diseases, both degenerative diseases and metabolic diseases, even though the food eaten is healthy food.